Quality not quantity for transglutaminase antibody 2: the performance of an endomysial and tissue transglutaminase test in screening coeliac disease remains stable over time. (3rd December 2012) - Swallow, K.; Wild, G.; Sargur, R.; Sanders, D. S.; Aziz, I.; Hopper, A. D.; Egner, W.
Summary National Institute of Clinical Excellence (NICE) and European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) guidance for the diagnosis of coeliac disease has been published. However, there is some controversy regarding the advice on the use of stratifying levels of immunoglobulin (IgA) tissue transglutaminase antibody (TG2) test positivity in the absence of test standardization and the vagueness of the indication to test equivocal samples. Using repeat service audit, we demonstrate that a combination of TG2 followed by IgA endomysial antibodies (EMA) is the best strategy for all degrees of mucosal abnormality using our test combination. Reliance upon immunoassay titre is not as effective, and cannot be applied consistently across populations in the absence of assay standardization. Guidelines advocating the use of tests should involve experts in laboratory diagnostics and external quality assurance to ensure that errors of generalization do not occur and that test performance is achievable in routine diagnostic use.